2022
DOI: 10.1155/2022/1713337
|View full text |Cite|
|
Sign up to set email alerts
|

Concurrent Hearing and Genetic Screening among Newborns in Ningbo, China

Abstract: Objective. To detect the carrier rates of deafness gene variants in populations in Ningbo and analyze the risk of hereditary hearing loss through concurrent hearing and genetic screening tests. Methods. Two thousand one hundred and seventy-four newborns were enrolled from November 2018 to August 2019. All subjects underwent hearing screening and newborn deafness genetic screening with 15 variants in 4 genes, and the positive sites were simultaneously verified by sequencing. Results. The total carrier rate of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Those studies that reported the use of AABR in the initial stage of screening either employed AABR solely for both stages50 or a combination of AABR and OAE to screen only high-risk newborns 20 52. Four studies from China used two-stage screening coupled with genetic hearing screening 21–23 25 53…”
Section: Resultsmentioning
confidence: 99%
“…Those studies that reported the use of AABR in the initial stage of screening either employed AABR solely for both stages50 or a combination of AABR and OAE to screen only high-risk newborns 20 52. Four studies from China used two-stage screening coupled with genetic hearing screening 21–23 25 53…”
Section: Resultsmentioning
confidence: 99%
“…This method is more suitable for screening many pathogenic genes and identifying new mutation sites without clear diagnostic information. Although microarray technology can detect more deafness-related mutation sites at the same time 9 , this method also requires a Microarray Scanner and detection system, which increases the cost of detection and can produce false positives and reduce the accuracy of detection 49 . Sanger sequencing, microarray chips, and WES detection methods also have a common problem: the lid of the reaction tube must be opened to remove the PCR products for follow-up testing, which increases the risk of laboratory contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, detection of deafness susceptibility genes is of great significance. At present, the common screening methods for deafness susceptibility genes are the melting curve 8 , gene chip (including the microarray method) 9 , Sanger sequencing 10 , and second-generation sequencing methods (including whole-exome sequencing, WES) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic mutation spectrum of hearing loss genes varies among different regions and ethnic populations caused by diverse genetic background ( 23 ). Several previous typical studies of common genetic screening of hearing loss among neonates in different areas of China were reviewed in Table 6 , including the screening method and tested spot numbers.…”
Section: Discussionmentioning
confidence: 99%